2023
DOI: 10.3389/fimmu.2023.1108895
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of local and systemic signature of eosinophilic esophagitis (EoE) in children through multi-omics approaches

Abstract: BackgroundEosinophilic oesophagitis (EoE) is a chronic food allergic disorder limited to oesophageal mucosa whose pathogenesis is still only partially understood. Moreover, its diagnosis and follow-up need repeated endoscopies due to absence of non-invasive validated biomarkers. In the present study, we aimed to deeply describe local immunological and molecular components of EoE in well-phenotyped children, and to identify potential circulating EoE-biomarkers.MethodsBlood and oesophageal biopsies were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In addition to the above-mentioned attempts, previous studies aiming at discovering common non-invasive indicators for EoE diagnosis, either failed in population testing, 9 , 63 scarcely tested in children, 64–66 or still staged in laboratory (ie, exosomes, esophageal microbiome, or non-targeted metabolomics). 67 For example, a panel of 8 cytokines (IL-4, IL-13, IL-5, IL-6, IL-12p70, CD40L, IL-1α, and IL-17) in plasma for identifying EoE has been tested but merely with a 61% sensitivity and 83% specificity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the above-mentioned attempts, previous studies aiming at discovering common non-invasive indicators for EoE diagnosis, either failed in population testing, 9 , 63 scarcely tested in children, 64–66 or still staged in laboratory (ie, exosomes, esophageal microbiome, or non-targeted metabolomics). 67 For example, a panel of 8 cytokines (IL-4, IL-13, IL-5, IL-6, IL-12p70, CD40L, IL-1α, and IL-17) in plasma for identifying EoE has been tested but merely with a 61% sensitivity and 83% specificity.…”
Section: Discussionmentioning
confidence: 99%
“… 74 Moreover, the evidence demonstrating the highly conserved transcriptomic signature of EoE in children subjects across different countries, genders, age, allergic status, and triggers, to some extent, favored the credibility of our conclusion. 9 , 75 , 76 The fact that EoE and GERD patients shared some similar clinical manifestations (ie, dysphagia, epigastric pain, food impactions, or prominent esophageal eosinophilia infiltration) and diagnosing EoE by the presence of ≥ 15 eos/high power field (x400) in the esophageal tissue biopsy or other eosinophilic biomarkers are not that solid, 7 makes this biomarker more important. 77 Prior studies have confirmed that pediatric EoE patients showed higher levels of Tregs in their esophageal epithelium than GERD patients and healthy children, 78–80 which was in opposite to adult EoE patients that had impaired induction of Tregs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations